SURGICAL METHODS AND POSTOPERATIVE COMPLICATIONS IN SEVERE ACUTE PANCREATITIS - D.S. SALIMOV; A.R. DOSTEV; S.G. ALI-ZADE; A.R. UMARI; A.M. KARIMOV (Паёми Сино, 2019)
The review article highlights the modern classification of acute pancreatitis, indications for the surgical treatment of severe, first of all, infected pancreonecrosis, development and the contentious issues of this problem. As you know, all surgical interventions in pancreonecrosis are divided into two types: radical and organ-preserving. This article examines the results of both methods with an analysis of the frequency of postoperative complications after each. In addition, two different methods of operations, «closed» and «open» – were evaluated to drain extraperitoneal space, taking into account the area of the necrotic process. Described the prospect of using Embryonal Natural Orifice Transluminal Endoscopic Surgery (ENOTES) in the treatment of severe acute pancreatitis, complicated by abdominal compartment syndrome. The frequency of intraoperative and early complications of «closed» and «open» interventions in severe acute pancreatitis, their recognition, prevention, and the choice is considered a method of surgical or conservative treatment.